2017
DOI: 10.1016/j.jvs.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular Versus Transaxillary First Rib Resection for Thoracic Outlet Obstruction: A Single-Institution Experience

Abstract: Objectives: Thoracic outlet syndrome (TOS) results from compression of the neurovascular structures supplying the upper extremity as they exit through the thoracic outlet. Depending on the clinical presentation, surgical decompression may be required. The transaxillary (TA) approach has been the preferred approach, although the supraclavicular (SC) approach has become more widely used, especially when adjunct procedures are required. Our objective was to review the results with both approaches in our instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Surgical options include first rib with cervical rib resection either via transaxillary or supraclavicular approaches with possible aneurysm resection and bypass graft placement (12). There are no distinct advantages or disadvantages to either approach although there are studies suggesting that supraclavicular approaches are associated with longer operative times (13).…”
Section: Cervical Rib Resectionmentioning
confidence: 99%
“…Surgical options include first rib with cervical rib resection either via transaxillary or supraclavicular approaches with possible aneurysm resection and bypass graft placement (12). There are no distinct advantages or disadvantages to either approach although there are studies suggesting that supraclavicular approaches are associated with longer operative times (13).…”
Section: Cervical Rib Resectionmentioning
confidence: 99%
“… 3 Several studies have shown no significant differences in outcomes between the transaxillary and supraclavicular approaches. 4 , 5 …”
mentioning
confidence: 99%